Monitoring the Social Attitudes of Foreign Students - M. B. Ponyavina; S. V. Rastorguev; P. S. Seleznev; A. A. Suchilina; A. B. Shatilov (Высшее образование в России)
It is necessary to monitor the social attitudes of foreign students in order to involve foreign applicants in a favorable to Russia discourse, applying the concept of “soft power”. Applicants’ social attitudes have a direct impact on the choice of the country of study and on the effectiveness of social, cultural, pedagogical adaptation of foreign students. The socio-cultural characteristics of foreign students were studied using focus groups, expert polls, and narrative interviews. The classification of foreign students according to cultural profiles has been made. Attitudes of students from different cultural profiles were monitored according to the questionnaires developed by the authors. Based on the scaling techniques of E. Bogardus, C. Osgood, L. Thurstone, L. Guttman, R. Likert, an integral index was calculated for each cultural profile. Methods for monitoring the social attitudes of foreign applicants make it possible to identify the specifics and dynamics of the attitudes of cultural profiles. Positive attitudes towards Russia contribute to the export of Russian educational services and attractiveness of the Russian cultural space and the educational system.